Pertarungan Elite Lokal dalam Menentukan Sistem Pemerintahan Nagari di Kabupaten Agam - Ujang Wardi; Aidinil Zetra; Asrinaldi. Asrinaldi. (Universitas Muhammadiyah Ponorogo, 2019)
The presence of Law No. 6 of 2014 as a form of central recognition of the regions, provides new opportunities for elitees at the local level in determining the choice of